HKMA-L adsorption material as well as preparation method and application thereof
HKMA-L adsorbent prepared by HKUST-1 composite MgAl-LDHs layered composite material solves the problem of low adsorption efficiency of hydrotalcite in antibiotics, achieves efficient removal of tetracycline and good reusability, and is suitable for industrial applications.
Patent Information
- Application Number
- CN202411508072.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, hydrotalcite has problems with particle aggregation, low adsorption efficiency and poor reproducibility in antibiotic adsorption, and the removal efficiency of tetracycline compounds is poor, making it difficult to apply on a large scale on industrial basis.
HKUST-1 composite MgAl-LDHs layered composite material is used to improve the adsorption site of the adsorbent through hydrogen bonding, electrostatic interaction and metal-organic complexing, and prepare HKMA-L adsorption material to achieve efficient removal of tetracycline. .
The efficient removal rate of tetracycline is achieved at 95.04%, and it has excellent reusability and stability. It has simple process and low cost, which is suitable for industrial production.
Smart Images

Figure CN119281289A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of treatment of wastewater containing antibiotics, and more specifically to a HKMA-L adsorption material, a preparation method and application thereof. Background Art
[0002] Tetracycline (TC) has been widely used in medicine, agriculture and animal husbandry to fight bacterial infections. Antibiotic contamination in ecosystems has attracted attention because of the hazards of antibiotics to humans, animals, plants and aquatic organisms. Due to overuse, a large amount of antibiotics have been released into the environment as a new type of pollutant. Residual antibiotics are persistent pollutants that are widely present in aquatic environments, and even trace amounts of antibiotics are not easily degraded in nature. Many reports have found that antibiotic residues exist in wastewater, sludge and wastewater treatment plants from pharmaceutical wastewater treatment plants, which may lead to the production of unwanted byproducts from ozone or chlorination during water treatment. These byproducts may be carcinogenic and toxic to ecosystems and humans.
[0003] At present, the main methods for treating antibiotic wastewater at home and abroad are adsorption, oxidation, photocatalysis and biodegradation. Among them, the adsorption method has attracted much attention due to its advantages of simple operation, low cost, high efficiency and environmental friendliness. Adsorption is generally divided into physical adsorption and chemical adsorption, and the commonly used adsorption materials are mainly: resin, primary amine compounds, carbon materials, etc. For example: Patent CN114906900A discloses a research result and material preparation method for removing cephalosporin antibiotics with an ion exchange resin, and the adsorption efficiency is relatively high, but the adsorption mechanism and material preparation are relatively complex; Patent CN 115999505 A provides a study on the adsorption performance of biochar on tetracycline and fluoroquinolone antibiotics, and the adsorption efficiency is relatively poor, and the preparation steps of the adsorbent are many; primary amine compounds are mostly studied for the adsorption of sulfonamide antibiotics; but these adsorbents have poor removal efficiency for tetracycline compounds. Therefore, it is necessary to find a new adsorbent with low cost, simple operation and high removal efficiency for tetracycline antibiotics.
[0004] Metal-organic frameworks (MOFs) are a type of crystalline porous material with a periodic network structure formed by the self-assembly of inorganic metal centers and bridging organic ligands. MOFs have the advantages of large specific surface area, regular porous morphology, and multiple metal sites. They are a new type of porous material developed in recent years and have been widely used in the field of chemistry and chemical engineering, such as gas storage, molecular separation, catalysis, and drug sustained release. Because of their large specific surface area, considering their performance, their adsorption performance can be fully developed, such as antibiotics, phosphates, and other substances that have a great impact on the environment.
[0005] At present, there are corresponding research progress in MOFs materials, and technical patents have been disclosed, but the research richness in the field of antibiotic adsorption is still lacking. For example, patent CN111686692 A provides a preparation method of antibiotic adsorption material of MIL-100 (Fe) doped with divalent cations, which is used to adsorb cephalosporin antibiotics, with significant effect and good adsorption effect, but it is limited to cephalosporin antibiotics and has a fixed application range; patent CN 106423064 A discloses a preparation method of magnesium-modified biomass, and the adsorbent has a certain adsorption effect on antibiotics, but the recovery process of the adsorbent is cumbersome, the recycling is poor, and the adsorption performance needs to be improved. Patent CN 111992257A discloses a preparation method of modified perovskite hollow porous microsphere material, which has good removal efficiency for antibiotics, but the preparation method is too complicated and difficult to prepare and apply on a large scale.
[0006] Hydrotalcite is an environmentally friendly inorganic material composed of positively charged (Mg 2+ 、Al 3+ , Ca 2+ 、Zn 2+ etc.) and the interlayer anions (such as CO 3 2- 、NO 3 - OH - Layered double metal hydroxides (such as hydrotalcite) assembled through non-covalent interactions were first discovered in natural hydrotalcite ore in schist layers. Studies have found that hydrotalcite has high interlayer anion exchange capacity, high specific surface area, adjustable charge density, and memory effect. At present, a large number of hydrotalcites have been used in the adsorption of dyes, heavy metal ions, antibiotics, etc. For example: Patent CN 113267522 A discloses a method for preparing a hydrotalcite material for uranyl ion adsorption; Patent CN 113134339 A discloses a method for preparing a hydrotalcite material doped with zirconium phosphate adsorption; Patent CN 115414915 A discloses a hydrotalcite-like adsorbent for recovering scandium and its preparation method.
[0007] However, in view of the defects of hydrotalcite in adsorption, such as particle aggregation, low adsorption efficiency and poor regeneration, composite modification of hydrotalcite has become the mainstream of research. However, at present, the modification of hydrotalcite still has technical problems such as complex operation and low adsorption efficiency, and there are few reports on the research of compounding HKUST-1 into hydrotalcite to improve adsorption performance. Summary of the invention
[0008] In view of this, the present invention provides a method for preparing a HKUST-1 composite MgAl-LDHs layered composite material for adsorbing tetracycline (TC) with simple process, low cost and good product performance.
[0009] One of the purposes of the present invention is to provide a HKMA-L adsorption material, which is a layered composite adsorption material of HKUST-1 composite MgAl-LDHs.
[0010] The inventive concept of the present invention is that LDHs are relatively negatively charged in their structure, and their special layered structure provides certain effective adsorption sites, which have the effect of removing positively charged substances such as antibiotics from water bodies. The present invention is aimed at the fact that hydrotalcite has a small adsorption capacity for pollutants in the prior art, so it is compounded with other adsorbents to improve the adsorption performance. HKUST-1 is a popular copper-containing MOF compound due to its high thermal stability, large surface area and large pore volume. Compounding it with LDHs changes its interlayer spacing. During the compounding process, through hydrogen bonding, electrostatic interaction and metal-organic complexation, the LDHs composite adsorbent (HKMA-L) obtains more adsorption sites, thereby giving HKMA-L good adsorption performance for TC. The adsorption mechanism is electrostatic attraction, pore filling process and π-π conjugation effect. HKMA-L shows excellent reusability and stability.
[0011] The second object of the present invention is to provide a method for preparing a HKMA-L adsorbent material, comprising the following steps:
[0012] S1. Preparation of HKUST-1
[0013] S11. The zinc oxide powder is evenly dispersed in deionized water, and ultrasonicated for 5-20 min to obtain zinc oxide nanocrystals for later use;
[0014] S12. Dissolve the divalent copper salt in deionized water to obtain a divalent copper salt solution for later use;
[0015] S13. 1,3,5-benzoic acid (H 3 BTC) is dissolved in anhydrous ethanol to obtain a 1,3,5-benzoic acid solution, and the zinc oxide nanocrystals, DMF, and the divalent copper salt solution are added to the 1,3,5-benzoic acid solution under stirring to generate a large amount of particle precipitation;
[0016] S14. The particle precipitate is washed several times with anhydrous ethanol and dried in a vacuum oven to obtain blue HKUST-1.
[0017] The beneficial effects of adopting the above process conditions are:
[0018] The chemicals used in this process are relatively cheap and easy to obtain, the reaction steps are simple and clear, the cost is low, it saves time and labor, and is convenient for industrial mass production.
[0019] S2. Preparation of HKMA-L adsorption material
[0020] S21. The divalent magnesium salt, trivalent aluminum salt and additive are dissolved in deionized water to obtain a solution A for later use;
[0021] S22. The HKUST-1 was ultrasonically dispersed in deionized water to obtain a solution B for later use;
[0022] S23. The solution B is added dropwise to the solution A and stirred at room temperature for 0.5-2h to obtain a mixed solution;
[0023] S24. The mixed solution was transferred to a 100 mL stainless steel reactor, heated in an oven at 100-200 ° C for 20-30 h, and cooled naturally to room temperature;
[0024] S25. Collect the light blue precipitate, wash it with deionized water and anhydrous ethanol three times respectively, vacuum dry it, and grind it into a light blue powder to obtain the HKMA-L adsorption material.
[0025] Preferably, in S11, the concentration of the zinc oxide powder in deionized water is 35-40 g / L.
[0026] Preferably, in S12, the divalent copper salt is selected from Cu(NO 3 ) 2 ·3H 2 O、CuSO 4 ·5H 2 O, CuCl 2 ·3H 2 O any one; the mass ratio of the zinc oxide powder to the divalent copper salt is 1:5-6, and the concentration of the divalent copper salt in deionized water is 200-230g / L.
[0027] Preferably, in S13, the mass ratio of the zinc oxide powder to the 1,3,5-benzoic acid is 1:1 to 1:3, and the concentration of the 1,3,5-benzoic acid in anhydrous ethanol is 50-60 g / L;
[0028] The liquid-to-solid ratio of the DMF to the 1,3,5-benzoic acid is 15-20 mL: 0.78-1 g.
[0029] The beneficial effects of using the above raw materials and raw material ratios are:
[0030] The reaction can be carried out at room temperature. After many tests, the results show that the product prepared by this raw material and raw material ratio has the highest adsorption efficiency.
[0031] Preferably, in S14, the vacuum drying is performed at 70-160° C. for 3-10 h.
[0032] Preferably, in S21, the divalent magnesium salt is selected from Mg(NO 3 )2 6H 2 O、MgSO 4 7H 2 O、MgCl 2 6H 2 O any one; the trivalent aluminum salt is selected from Al(NO 3 ) 3 6H 2 O、Al 2 (SO 4 ) 3 12H 2 O、AlCl 3 6H 2 O any one; the auxiliary agent is selected from any one of urea and hexamethylenetetramine;
[0033] The concentration of the divalent magnesium salt in the solution A is 40-50 g / L, the mass ratio of the divalent magnesium salt to the trivalent aluminum salt is 1:1-3:1, and the mass ratio of the divalent magnesium salt to the auxiliary agent is 1:1-5:1.
[0034] Preferably, the concentration of HKUST-1 in the solution B in S22 is 35-45 g / L.
[0035] The beneficial effects of using the above raw materials and raw material ratios are:
[0036] After many tests, the results show that the product prepared with this raw material and raw material ratio has the highest adsorption efficiency.
[0037] Preferably, in steps S14 and S25, the vacuum drying is performed at 50-160° C. for 3-20 hours.
[0038] Preferably, in step S25, the particle size of the HKMA-L adsorption material is 100-200 mesh.
[0039] The third object of the present invention is to provide an application of HKMA-L adsorption material in adsorbing tetracycline.
[0040] It can be seen from the above technical solution that, compared with the prior art, the beneficial effects achieved by the present invention are:
[0041] (1) The main raw materials for synthesizing the modified hydrotalcite-like substance of the present invention are inorganic salts and urea, which are widely available and low in cost.
[0042] (2) The preparation process and operation of the synthetic modified hydrotalcite-like product of the present invention are very simple, the preparation cycle is short, the product is non-toxic, environmentally friendly, does not require special chemical equipment, and is easy to realize industrial production.
[0043] (3) The modified hydrotalcite of the present invention has a relatively high removal rate for tetracycline pollutants; by further studying the effect of its doping ratio on the adsorbent performance, the optimal doping ratio was determined, and its adsorption effect on tetracycline was significantly increased, with a removal rate of 95.04%. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0045] Figure 1 This is a scanning electron microscope image of the HKUST-1 hydrotalcite layered composite material of Example 4.
[0046] Figure 2 This is the infrared spectrum of the HKUST-1 hydrotalcite layered composite material of Example 3.
[0047] Figure 3 This is the adsorption curve of TC by the HKUST-1 hydrotalcite layered composite material of Example 2.
[0048] Figure 4 This is a bar chart showing the relationship between the number of reuses and the removal rate of the HKUST-1 hydrotalcite layered composite material of Example 1. DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Example 1
[0051] A preparation method of HKUST-1 composite MgAl-LDHs layered composite material with high efficiency in adsorbing tetracycline (TC):
[0052] 0.3150g zinc oxide powder was dispersed in 8ml deionized water and ultrasonicated for 9min to form zinc oxide nanocrystals. Then 1.7400g CuCl 2 ·3H 2 O was dissolved in 8 mL of deionized water, and 0.8775 g of 1,3,5-benzoic acid (H 3 BTC) was dissolved in 16 mL of ethanol; again, the mixture was stirred in H3 Zinc oxide nanocrystals, 20 mL of DMF, and divalent copper salt solution were added to the BTC solution. After a large number of particles appeared, they were washed several times by centrifugation with ethanol; finally, they were dried in a vacuum oven at 120°C for 6 h to obtain a blue sample (HKUST-1).
[0053] 3.0021 g Mg(NO 3 ) 2 7H 2 O, 1.9874 g Al 2 (SO 4 ) 3 12H 2 O, 0.8943g urea was dissolved in 65mL water, called solution A; 0.8690g HKUST-1 was placed in 20mL water for ultrasonic dispersion, called solution B, then solution B was added dropwise to solution A, stirred at room temperature for 1h, then the mixed solution was transferred to a 100mL stainless steel reactor, and heated at 135℃ (oven) for 26h, then air-cooled to room temperature, light blue precipitates were collected, and washed 3 times with deionized water and anhydrous ethanol respectively. Then the sample was dried at 80℃ for 18h to obtain a light blue solid, which was ground into a light blue powder. That is, HKUST-1 / MgAl-LDHs (HKMA-L) product.
[0054] Prepare 25mg / L TC solution, measure the absorbance at 357nm wavelength to draw a standard curve. At room temperature (25℃), put 0.05g HKMA-L in 50mL TC solution of a certain concentration. Oscillate in a shaker for 60min, filter the supernatant with a 0.45μm filter membrane to remove impurities, and take the filtrate to measure the TC concentration at 375nm wavelength.
[0055] The adsorbent has a removal rate of 95.00% for TC and an adsorption capacity of 23.65 mg / g.
[0056] Example 2
[0057] A preparation method of HKUST-1 composite MgAl-LDHs layered composite material with high efficiency in adsorbing tetracycline (TC):
[0058] 0.3030 g of zinc oxide powder was dispersed in 8 ml of deionized water and ultrasonicated for 8 min to form zinc oxide nanocrystals. Then 1.8100 g of CuSO 4 ·5H 2 O was dissolved in 8 mL of deionized water, and 0.7900 g of 1,3,5-benzoic acid (H 3 BTC) was dissolved in 15 mL of ethanol; again, the mixture was stirred in H 3 Add zinc oxide nanocrystals, 19 mL DMF, and CuSO4 ·5H 2 O solution, and after a large number of particles appeared, it was washed several times by centrifugation with ethanol; finally, it was dried in a vacuum oven at 140°C for 5 h to obtain a blue sample (HKUST-1).
[0059] 2.4522 g MgSO 4 7H 2 O, 1.6720 g Al(NO 3 ) 3 6H 2 O, 0.8432g urea was dissolved in 50mL water, called solution A; 0.8300g HKUST-1 was placed in 20mL water for ultrasonic dispersion, called solution B, then solution B was added dropwise to solution A, stirred at room temperature for 1h, then the mixed solution was transferred to a 100mL stainless steel reactor, and heated at 130℃ (oven) for 26h, then air-cooled to room temperature, light blue precipitates were collected, and washed with deionized water and anhydrous ethanol for 3 times each. Then the sample was dried at 60℃ for 27h to obtain a light blue solid, which was ground into a light blue powder. That is, HKUST-1 / MgAl-LDHs (HKMA-L) product.
[0060] Prepare 35mg / L TC solution, measure the absorbance at 357nm wavelength to draw a standard curve. At room temperature (25℃), put 0.07g HKMA-L in 50mL TC solution of a certain concentration. Oscillate in a shaker for 90min, filter the supernatant with a 0.45μm filter membrane to remove impurities, and take the filtrate to measure the TC concentration at 375nm wavelength.
[0061] The removal rate of TC by the adsorbent is 88.00%, and the adsorption capacity can reach 30.08 mg / g.
[0062] Example 3
[0063] A preparation method of HKUST-1 composite MgAl-LDHs layered composite material with high efficiency in adsorbing tetracycline (TC):
[0064] 0.3271g zinc oxide powder was dispersed in 9ml deionized water and ultrasonicated for 6min to form zinc oxide nanocrystals. Then 1.7400g Cu(NO 3 ) 2 ·3H 2 O was dissolved in 8 mL of deionized water, and 0.8400 g of 1,3,5-benzoic acid (H 3 BTC) was dissolved in 16 mL of ethanol; again, the mixture was stirred in H 3 Add zinc oxide nanocrystals, 17 mL DMF, and CuCl 2 ·3H 2O solution, and after a large number of particles appeared, it was washed several times by centrifugation with ethanol; finally, it was dried at 135°C in a vacuum oven for 8 h to obtain a blue sample (HKUST-1).
[0065] 3.1983 g MgCl 2 7H 2 O, 1.7082 g Al 2 (SO 4 ) 3 12H 2 O, 0.9529g urea was dissolved in 65mL water, called solution A; 0.8300g HKUST-1 was placed in 20mL water for ultrasonic dispersion, called solution B, then solution B was added dropwise to solution A, stirred at room temperature for 1h, then the mixed solution was transferred to a 100mL stainless steel reactor, and heated at 170℃ (oven) for 23h, then air-cooled to room temperature, light blue precipitates were collected, and washed 3 times with deionized water and anhydrous ethanol respectively. Then the sample was dried at 70℃ for 23h to obtain a light blue solid, which was ground into a light blue powder. That is, HKUST-1 / MgAl-LDHs (HKMA-L) product.
[0066] Prepare 25mg / L TC solution, measure the absorbance at 357nm wavelength to draw a standard curve. At room temperature (25℃), put 0.03g HKMA-L in 50mL TC solution of a certain concentration. Oscillate in a shaker for 90min, filter the supernatant with a 0.45μm filter membrane to remove impurities, and take the filtrate to measure the TC concentration at 375nm wavelength.
[0067] The removal rate of TC by the adsorbent is 94.08%, and the adsorption capacity can reach 23.50 mg / g.
[0068] Example 4
[0069] A preparation method of HKUST-1 composite MgAl-LDHs layered composite material with high efficiency in adsorbing tetracycline (TC):
[0070] 0.2800g zinc oxide powder was dispersed in 7ml deionized water and ultrasonicated for 5min to form zinc oxide nanocrystals. Then 1.6800g Cu(NO 3 ) 2 ·3H 2 O was dissolved in 8 mL of deionized water, and 0.8300 g of 1,3,5-benzoic acid (H 3 BTC) was dissolved in 16 mL of ethanol; again, the mixture was stirred in H 3 Zinc oxide nanocrystals, 16 mL DMF, Cu(NO 3 ) 2 ·3H 2O solution, after a large number of particles appeared, it was washed several times by centrifugation with ethanol; finally, it was dried in a vacuum oven at 145°C for 4.5h to obtain a blue sample (HKUST-1)
[0071] 3.0021 g Mg(NO 3 ) 2 7H 2 O, 1.9874 g Al 2 (SO 4 ) 3 12H 2 O, 0.8943g urea was dissolved in 62mL water, called solution A; 0.7990g HKUST-1 was placed in 20mL water for ultrasonic dispersion, called solution B, then solution B was added dropwise to solution A, stirred at room temperature for 1h, then the mixed solution was transferred to a 100mL stainless steel reactor, and heated at 140℃ (oven) for 25h, then air-cooled to room temperature, light blue precipitates were collected, and washed with deionized water and anhydrous ethanol for 3 times each. Then the sample was dried at 110℃ for 14h to obtain a light blue solid, which was ground into a light blue powder. That is, HKUST-1 / MgAl-LDHs (HKMA-L) product.
[0072] Prepare 25mg / L TC solution, measure the absorbance at 357nm wavelength to draw a standard curve. At room temperature (25℃), put 0.05g HKMA-L in 50mL TC solution of a certain concentration. Oscillate in a shaker for 120min, filter the supernatant with a 0.45μm filter membrane to remove impurities, and take the filtrate to measure the TC concentration at 375nm wavelength.
[0073] The removal rate of TC by the adsorbent is 95.00%, and the adsorption capacity can reach 23.66 mg / g.
[0074] Example 5
[0075] A preparation method of HKUST-1 composite MgAl-LDHs layered composite material with high efficiency in adsorbing tetracycline (TC):
[0076] 0.3576g zinc oxide powder was dispersed in 10ml deionized water and ultrasonicated for 10min to form zinc oxide nanocrystals. Then 1.8380g CuSO 4 ·5H 2 O was dissolved in 8 mL of deionized water, and 0.9000 g of 1,3,5-benzoic acid (H 3 BTC) was dissolved in 16 mL of ethanol; again, the mixture was stirred in H 3 Zinc oxide nanocrystals, 18 mL DMF, Cu(NO 3 ) 2 ·3H2 O solution, after a large number of particles appeared, it was washed several times by centrifugation with ethanol; finally, it was dried in a vacuum oven at 150°C for 4 h to obtain a blue sample (HKUST-1)
[0077] 2.1810 g Mg(NO 3 ) 2 7H 2 O, 1.8750 g Al(NO 3 ) 3 9H 2 O, 1.0500g urea was dissolved in 50mL water, called solution A; 0.8000g HKUST-1 was placed in 20mL water for ultrasonic dispersion, called solution B, then solution B was added dropwise to solution A, stirred at room temperature for 1h, then the mixed solution was transferred to a 100mL stainless steel reactor, and heated at 145℃ (oven) for 21h, then air-cooled to room temperature, light blue precipitates were collected, and washed with deionized water and anhydrous ethanol for 3 times each. Then the sample was dried at 100℃ for 15h to obtain a light blue solid, which was ground into a light blue powder. That is, HKUST-1 / MgAl-LDHs (HKMA-L) product.
[0078] Prepare 28mg / L TC solution, measure the absorbance at 357nm wavelength to draw a standard curve. At room temperature (25℃), put 0.06g HKMA-L in 50mL TC solution of a certain concentration. Oscillate in a shaker for 90min, filter the supernatant with a 0.45μm filter membrane to remove impurities, and take the filtrate to measure the TC concentration at 375nm wavelength.
[0079] The removal rate of TC by the adsorbent is 94.28%, and the adsorption capacity can reach 22.40 mg / g.
[0080] Example 6
[0081] A preparation method of HKUST-1 composite MgAl-LDHs layered composite material with high efficiency in adsorbing tetracycline (TC):
[0082] 0.4000g zinc oxide powder was dispersed in 10ml deionized water and ultrasonicated for 10min to form zinc oxide nanocrystals. Then 2.3000g CuCl 2 ·3H 2 O was dissolved in 10 mL of deionized water, and 0.8600 g of 1,3,5-benzoic acid (H 3 BTC) was dissolved in 16 mL of ethanol; again, the mixture was stirred in H 3 Add zinc oxide nanocrystals, 18 mL DMF, and CuCl 2 ·3H 2O solution, after a large number of particles appeared, it was washed several times by centrifugation with ethanol; finally, it was dried in a vacuum oven at 125℃ for 5.5h to obtain a blue sample (HKUST-1)
[0083] 3.0000g Mg(NO 3 ) 2 7H 2 O, 1.8902 g Al 2 (SO 4 ) 3 12H 2 O, 0.7991g urea was dissolved in 64mL water, called solution A; 0.8100g HKUST-1 was placed in 20mL water for ultrasonic dispersion, called solution B, then solution B was added dropwise to solution A, stirred at room temperature for 1h, then the mixed solution was transferred to a 100mL stainless steel reactor, and heated at 160℃ (oven) for 24h, then air-cooled to room temperature, light blue precipitates were collected, and washed 3 times with deionized water and anhydrous ethanol respectively. Then the sample was dried at 90℃ for 16h to obtain a light blue solid, which was ground into a light blue powder. That is, HKUST-1 / MgAl-LDHs (HKMA-L) product.
[0084] Prepare 20mg / L TC solution, measure the absorbance at 357nm wavelength to draw a standard curve. At room temperature (25℃), put 0.05g HKMA-L in 50mL TC solution of a certain concentration. Oscillate in a shaker for 120min, filter the supernatant with a 0.45μm filter membrane to remove impurities, and take the filtrate to measure the TC concentration at 375nm wavelength.
[0085] The removal rate of TC by the adsorbent is 94.88%, and the adsorption capacity can reach 22.46 mg / g.
[0086]
Macro and micro morphology
[0087] The morphology of HKUST-1 composite MgAl-LDHs layered composites was observed by scanning electron microscopy. The surfaces of the prepared HKUST-1 crystals appeared relatively smooth.
[0088] HKUST-1 (see Figure 1 a) shows the octahedral shape characteristic of this particular MOFs, which is consistent with the results in the literature. Figure 1 b) The sample is a hexagonal plate-like structure with a lamellar structure. The plate is thick and relatively flat, and the particle size is uniform, which is a typical hydrotalcite structure. Since HKUST-1 is in situ generated on the hexagonal plate-like structure of hydrotalcite, HKUST-1 exhibits an octahedral structure smaller than the original size, stacked between the MgAl-LDHs sheets, and assembled to form HKMA-L (see Figure 1 c) The thickness of each HKMA-L sheet is about 5 to 10 nm. Compared with the original MgAl-LDHs, the morphology of HKMA-L is a lotus-shaped structure in which the octahedral structure of HKUST-1 grows more evenly on the hexagons of hydrotalcite. The lotus-shaped composite structure has a larger specific surface area and more abundant active sites, which promotes the more effective enrichment of pollutants on the adsorbent surface, making it have a more effective adsorption effect.
[0089]
Infrared spectroscopy analysis
[0090] The infrared absorption spectrum of the composite HKUST-1 hydrotalcite layered composite is shown below.
[0091] It can be seen from the figure that for this material 3500cm -1 is the stretching vibration peak of -OH and water molecules between hydrotalcite layers, 1600 cm -1 is the bending vibration between water molecules, 1375cm -1 、821cm -1 For CO 3 2- The stretching vibration and bending vibration of the -1 Some peaks in the region are caused by lattice vibration; from the infrared spectrum of MgAl-LDHs, it can be seen that at 3500cm -1 is the stretching vibration peak of -OH and water molecules between hydrotalcite layers, 1375 cm -1 、821cm -1 For CO 3 2- Stretching and bending vibration, 400~1000cm -1 It is caused by lattice vibration. From the infrared spectrum of HKUST-1, we can see that at 3400cm -1 The C=O stretching vibration of the carboxyl group on the benzene ring is caused by the stretching vibration of the C=O group on the benzene ring, which is between 1400 and 1600 cm -1 It is the CC stretching vibration within the benzene ring.
[0092] The infrared spectrum of HKMA-L and the infrared spectrum of MgAl-LDHs and HKUST-1 are basically similar. It can be concluded that the composite degree of HKUST-1 and MgAl-LDH is intact.
[0093]
Adsorption concentration performance
[0094] Take 0.05g of HKMA-L and add it to 50mL of TC with different initial concentrations. Keep the pH of the original solution and the temperature at 25℃. Shake it on a shaker for a certain period of time. Detect the TC content by UV-visible spectrophotometry and calculate the removal rate.
[0095] The adsorption capacity of HKMA-L for different initial TC concentrations is shown in the figure. As shown in the figure, as the concentration increases, the adsorption capacity of HKMA-L increases and the removal rate decreases. When the initial concentration is from 20 to 50 mg / L, the removal rate decreases from 95.00% to 86.27%. However, as the concentration increases, the adsorption capacity of HKMA-L for TC increases from 19.00 mg / g to 43.13 mg / g. This shows that as the concentration increases, the number of TC molecules increases, the effective adsorption sites gradually decrease, and the adsorption of TC decreases significantly, which depends on the reduction of surface vacancies. It shows that the HKUST-1 composite MgAl-LDHs layered composite material has good removal performance for TC.
[0096] [Reusable performance]
[0097] In order to explore the recycling performance of HKMA-L, the HKMA-L that had adsorbed TC was washed with ethanol to remove the free TC on the surface, and then washed with HNO 3 (1mol / L) desorption. After desorption, wash with distilled water to neutrality, dry, and use for the next adsorption test. The removal rate of the first adsorption was 95.05%, and the removal rate of the second cycle reached 88.56%, and the adsorption efficiency decreased slightly. When it was cycled to the fourth time, the removal rate dropped to 80.36%. This may be due to the loss of adsorbent, the consumption of effective adsorption sites, and the insufficient release of TC by saturated adsorbent. This shows that HKMA-L has good reusability.
[0098] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A HKMA-L adsorption material, characterized in that: The HKMA-L adsorption material is a layered composite adsorption material of HKUST-1 and MgAl-LDHs.
2. A method for preparing HKMA-L adsorbent material, characterized in that: The following steps are involved: S1. Preparation of HKUST-1 S11. The zinc oxide powder is evenly dispersed in deionized water to obtain zinc oxide nanocrystals for later use; S12. Dissolve the divalent copper salt in deionized water to obtain a divalent copper salt solution for later use; S13. dissolving 1,3,5-benzoic acid in anhydrous ethanol to obtain a 1,3,5-benzoic acid solution, and adding the zinc oxide nanocrystals, DMF, and the divalent copper salt solution to the 1,3,5-benzoic acid solution under stirring to generate a precipitate; S14. The precipitate is washed with anhydrous ethanol and dried in vacuo to obtain HKUST-1; S2. Preparation of HKMA-L adsorption material S21. The divalent magnesium salt, trivalent aluminum salt and additive are dissolved in deionized water to obtain a solution A for later use; S22. The HKUST-1 was ultrasonically dispersed in deionized water to obtain a solution B for later use; S23. The solution B is added dropwise to the solution A and stirred at room temperature for 0.5-2h to obtain a mixed solution; S24. The mixed solution is heated at 100-200 ° C for 20-30h and naturally cooled to room temperature; S25. The precipitate was collected, washed with deionized water and anhydrous ethanol for three times respectively, vacuum dried and ground to obtain HKMA-L adsorption material.
3. The method for preparing a HKMA-L adsorption material according to claim 2, characterized in that: In S11, the concentration of the zinc oxide powder in deionized water is 35-40 g / L.
4. The method for preparing a HKMA-L adsorption material according to claim 2, characterized in that: In S12, the divalent copper salt is selected from any one of Cu(NO3)2·3H2O, CuSO4·5H2O, and CuCl2·3H2O; The mass ratio of the zinc oxide powder to the divalent copper salt is 1:5-6, and the concentration of the divalent copper salt in deionized water is 200-230 g / L.
5. The method for preparing a HKMA-L adsorption material according to claim 2, characterized in that: In S13, the mass ratio of the zinc oxide powder to the 1,3,5-benzoic acid is 1:1 to 1:3, and the concentration of the 1,3,5-benzoic acid in anhydrous ethanol is 50-60 g / L; The liquid-to-solid ratio of the DMF to the 1,3,5-benzoic acid is 15-20 mL: 0.78-1 g.
6. The method for preparing a HKMA-L adsorption material according to claim 2, characterized in that: In S21, the divalent magnesium salt is selected from any one of Mg(NO3)2·6H2O, MgSO4·7H2O, and MgCl2·6H2O; The trivalent aluminum salt is selected from any one of Al(NO3)3·6H2O, Al2(SO4)3·12H2O, and AlCl3·6H2O; the auxiliary agent is selected from any one of urea and hexamethylenetetramine; The concentration of the divalent magnesium salt in the solution A is 40-50 g / L, the mass ratio of the divalent magnesium salt to the trivalent aluminum salt is 1:1-3:1, and the mass ratio of the divalent magnesium salt to the auxiliary agent is 1:1-5:
1.
7. The method for preparing a HKMA-L adsorption material according to claim 2, characterized in that: The concentration of HKUST-1 in the solution B is 35-45 g / L.
8. The method for preparing a HKMA-L adsorption material according to claim 2, characterized in that: In steps S14 and S25, the vacuum drying is performed at 50-160° C. for 3-20 hours.
9. The method for preparing a HKMA-L adsorption material according to claim 2, characterized in that: In step S25, the particle size of the HKMA-L adsorption material is 100-200 mesh.
10. An application of HKMA-L adsorption material, characterized in that: The invention relates to an application of the HKMA-L adsorption material according to claim 1 or the HKMA-L adsorption material obtained by any one of the preparation methods according to claims 2 to 9 in adsorbing tetracycline.
Citation Information
Patent Citations
Magnesium modified biomass and application thereof
CN106423064A
Modified perovskite hollow porous microsphere for catalytic degradation of antibiotics, and preparation method and application thereof
CN111992257A
Preparation of zirconium-doped hydrotalcite-like adsorbent and application of zirconium-doped hydrotalcite-like adsorbent in treatment of phosphorus-containing wastewater
CN113134339A
Hydrotalcite preparation and uranyl ion adsorption exploration method
CN113267522A
Application of ion exchange resin containing sulfonic acid-phosphate bifunctional groups to removal of cephalosporin antibiotics
CN114906900A